2018
DOI: 10.1039/c8ce00113h
|View full text |Cite
|
Sign up to set email alerts
|

Low dimensional solids based on Mo6cluster cyanides and Mn2+, Mn3+or Cd2+metal ions: crystal chemistry, magnetic and optical properties

Abstract: Five new cluster compounds based on [Mo6Bri8(CN)a6]2− and [Mo6Bri6Qi2(CN)a6]n− (Q = S, Se, n = 3, 4) cluster units have been synthesized and characterized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 77 publications
1
4
0
Order By: Relevance
“…Each Mo atom of the cluster core is coordinated by apical CN − ligand. The Mo-C distances display the average length of 2.188(8) Å, which is in the range of values that were reported for hexanuclear cyanide clusters of Mo [ 32 , 43 , 44 ]. The crystal packing includes the cluster anions forming a column along the a axis and Bu 4 N + cations, which fill the space between anions forming a cationic sublattice with channel cavities ( Figure 4 b).…”
Section: Resultssupporting
confidence: 68%
See 2 more Smart Citations
“…Each Mo atom of the cluster core is coordinated by apical CN − ligand. The Mo-C distances display the average length of 2.188(8) Å, which is in the range of values that were reported for hexanuclear cyanide clusters of Mo [ 32 , 43 , 44 ]. The crystal packing includes the cluster anions forming a column along the a axis and Bu 4 N + cations, which fill the space between anions forming a cationic sublattice with channel cavities ( Figure 4 b).…”
Section: Resultssupporting
confidence: 68%
“…Until now, only one structure of a cyanide cluster based on halide octahedral molybdenum core has been reported, namely [Mo 6 Br 8 (CN) 6 ] 2− [ 31 ]. It was shown that this complex formed polymeric compounds with transition metal cations [ 32 ]. For octahedral tungsten halides, cyanide compounds have not been described.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1d) with cyanide ligands (O1…N2 = 3.33(1)Å, symmetry code for N2: 1-x, -y, 1-z). As calculated by the program PLATON, [12] the effective free volume in 1 is 88.5 Å 3 corresponding to 6.5% of the crystal volume. When crystals of 1 are heated at 180 °C for 30 min, the solvent (MeOH) is removed to form (1') which has the same layered framework as (1).…”
Section: Resultsmentioning
confidence: 99%
“…When the terminal ligands are equipped with suitable ditopic ligands, the clusters can be used as building blocks together with simple metal ions or coordinatively unsaturated complexes for the preparation of supramolecular assemblies or polymeric architecture. [11][12] For example, our group has focused on using edge-caped octahedral [Nb 6 Cl 12 (CN) 6 ] 4− cluster and transition metal complexes as building blocks. 13 Most reported cluster-containing molecular assemblies are based on {Re 6 }, {W 6 }, {Mo 6 }, {Zr 6 } and {Nb 6 } cluster units.…”
Section: Introductionmentioning
confidence: 99%